Evaporative Water Loss and Stopover Behavior in Three Passerine Bird Species During Autumn Migration - Paces, Bernhard; Waringer, Barbara M.; Domer, Adi; Burns, Darren; Zvik, Yoram; Wojciechowski, Michał S.; Shochat, Eyal; Sapir, Nir; Maggini, Ivan (Frontiers in Ecology and Evolution, 2021)
Migratory birds are often not specifically adapted to arid conditions, yet several species travel across deserts during their journeys, and often have more or less short stopovers there. We investigated whether differences in thermoregulatory mechanisms, specifically evaporative cooling, explain the different behavior of three passerine species while stopping over in the Negev desert, Israel. We measured cutaneous water loss (CWL) under ambient conditions and the temperature of panting onset in an experimental setup. In addition, we performed behavioral observations of birds at a stopover site where we manipulated water availability. Blackcaps had slightly higher CWL at relatively low temperatures than Willow Warblers and Lesser Whitethroats. When considered relative to total body mass, however, Willow Warblers had the highest CWL of the three species. Blackcaps started panting at lower ambient temperature than the other two species. Taken together, these results suggest that Willow Warblers are the most efficient in cooling down their body, possibly with the cost of needing to regain water by actively foraging during their staging. Lesser Whitethroats had a similar pattern, which was reflected in their slightly higher levels of activity and drinking behavior when water was available. However, in general the behavior of migratory species was not affected by the availability of water, and they were observed drinking rather rarely. Our results indicate that differences in thermoregulatory mechanisms might be at the basis of the evolution of different stopover strategies of migratory birds while crossing arid areas such as deserts.